Relative antioxidant activity of Brazilian medicinal plants for gastrointestinal diseases - Bonacorsi, Cibele [UNESP]; da Fonseca, Luiz Marcos [UNESP]; Raddi, Maria Stella G. [UNESP]; Kitagawa, Rodrigo R.; Sannomiya, Miriam; Vilegas, Wagner [UNESP] (Academic Journals, 2011)
The free radical scavenging capacity of Brazilian medicinal plants and some of their constituents was examined in vitro using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) quantitative assay. Twelve medicinal plants, used to treat gastrointestinal disorders (Alchornea glandulosa, Alchornea triplinervia, Anacardium humile, Byrsonima crassa, Byrsonima cinera, Byrsonima intermedia, Davilla elliptica, Davilla nitida, Mouriri pusa, Qualea grandiflora, Qualea parviflora and Qualea multiflora), were selected because they showed antiulcerogenic activity in previous studies. The radical scavenging methanolic extracts activity demonstrated to be dose-dependent. The efficient concentration, which represents the amount of the antioxidant able of decrease the initial DPPH radical by 50%, vary from < 5 to 17.2 mu g/ml. The lowest efficient concentration values among the analyzed plant were shown by A. humile, B. crassa and Q. parviflora. Purified phenolic compounds (amentoflavone, (+)-catechin, methyl gallate, quercetin 3-O-alpha-L-arabinopyranoside, and quercetin 3-O-beta-D-galactopyranoside) were also tested and the greatest antioxidant activities were obtained with (+)-catechin and methyl gallate, similar to quercetin, a phenolic compound used as standard.
Keywords: Brazilian medicinal plants; antioxidant activity; 2,2-diphenyl-1-picrylhydrazyl (DPPH); gastric ulcers